2015
DOI: 10.1007/s00394-015-1120-x
|View full text |Cite
|
Sign up to set email alerts
|

Lebanese children are iodine deficient and urinary sodium and fluoride excretion are weak positive predictors of urinary iodine

Abstract: Lebanese elementary school children are iodine deficient due to inadequately iodized salt. The weak correlation between UIC and urinary sodium suggests most dietary iodine does not come from iodized salt. The poor correlation between UIC and urinary fluoride suggests that fluoride intake is not affecting iodine metabolism. Efforts are needed in Lebanon to improve industry compliance with salt fortification through improved monitoring and enforcement of legislation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…As found in other studies (Ategbo, Sankar, Schultink, van der Haar, & Pandav, ; Ghattas et al, ; Rohner et al, ), the iodine status in Madagascar appears to be partly associated with the salt iodine content at the household level.…”
Section: Discussionsupporting
confidence: 74%
“…As found in other studies (Ategbo, Sankar, Schultink, van der Haar, & Pandav, ; Ghattas et al, ; Rohner et al, ), the iodine status in Madagascar appears to be partly associated with the salt iodine content at the household level.…”
Section: Discussionsupporting
confidence: 74%
“…This prevalence is similar to the one observed in the Spanish population [ 13 ] (which is 3.7%), but lower than the ones reported in the adolescent population of the NHANES III study [ 5 ] (which is, resp., 6.3% and 4.8% for Tg-Ab and TPO-Ab). This lower prevalence in our study compared to that in the US population could be related to an insufficient iodine intake [ 15 ], since iodine excess is a known risk factor for autoimmune thyroid disease [ 26 , 27 ]. In addition, we found that the presence of thyroid antibodies is a determinant of TSH values in girls but not in boys.…”
Section: Discussionmentioning
confidence: 69%
“…The higher cutoff used in this last study may explain part of this difference. Lower iodine status in Lebanese children [ 15 ] or genetic/ethnic factors could also be behind this, since both factors were found to affect the TSH reference interval [ 16 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no published data in Lebanon regarding screening protocols or rates of CH among VLBW infants. Based on reports of mild iodine deficiency in Lebanon [26], we hypothesized that the incidence rates of CH among VLBW preterm infants are higher than the ones reported in the literature. The aims of this study were: (1) to survey the compliance rates with screening guidelines for CH and for late TSH rise among VLBW infants at a tertiary care center in Lebanon; (2) to determine the incidence rates of CH and of late-rise TSH in this population over a 6-year period and to explore the associated risk factors.…”
Section: Introductionmentioning
confidence: 74%
“…According to the 2004 WHO global database, Lebanon falls in the mild iodine deficiency category [30]. Recent studies indicate mild iodine deficiency in Lebanese school age children [26]. Although there are no published data on the status of pregnant and lactating women in Lebanon, one could assume by extrapolation that they may fall into this category.…”
Section: Discussionmentioning
confidence: 99%